Evaluation of anthocyanin.rich standardised extract of hlbrscus sabdariffa l. niosomes formulation as anti- hypercholesterol and cardioprotective: a pilot study - Edwin, Mohd Azmie (2020)
Hypercholesterolaemia increased the risk of developing cardiovascular diseases (CVDs), chronic kidney diseases (CKDs) and liver disorder. Hibiscus sabdariffa L. (Roselle) has been used traditionally to reduce weight and cholesterol level. Roselle has been shown to have a higher content of anthocyanin. Anthocyanin has been shown to have anti-hypercholesterol and cardioprotective effect. However, the therapeutic application of Roselle might be impeded by its shortcomings such as low stability, poor pharmacokinetics properties of anthocyanin in the extract causing administration at therapeutic dose unrealistic. The present study aims to evaluate effects of the anthocyanin-rich standardised aqueous extract of Roselle using niosomes formulation (AEHS-Nio) on hypercholesterolaemia (HC) rat. Rats were induced to be HC for 4 weeks. There are three phases planned for this study. The first phase (induction phase) was designed to develop a HC rat model using a self-made HCD diet followed by the second phase (intervention phase) after the first phase to assess the effects of AEHSNio on body mass index (BMI), total cholesterol (TC) levels and systolic blood pressure (SBP) in the rat. Lastly, the third phase where the rats will myocardial infarction induced (HC-MI) at days 29 and 30 using isoprenaline to evaluate whether AEHS-Nio able to protect the heart by improving the histological aspect and the biochemical markers of damaged heart secondary to MI. Roselle extracts were expected to improve the preventive impact of hypercholesterolaemia despite minor improvement in the morphology of aorta, kidney and liver. In addition, AEHS-Nio will also able to prevent the damage to the heart secondary to MI. Collectively, these results were expected to be able to show that AEHS-Nio potentially can be utilised as treatment and prevention of hypercholesterolaemia as well as an adjuvant treatment as the cardioprotective.